Oral nomegestrol acetate and transdermal 17-beta-estradiol for preventing post-partum relapses in multiple sclerosis: The POPARTMUS study. (August 2021) - Vukusic, Sandra; Ionescu, Iuliana; Cornu, Catherine; Bossard, Nadine; Durand-Dubief, Françoise; Cotton, François; Durelli, Luca; Marignier, Romain; Gignoux, Laurence; Laplaud, David-Axel; Moreau, Thibault; Clavelou, Pierre; et al.
Background: Sex steroids could explain the course of multiple sclerosis (MS) in pregnancy. Objective: To compare the annualized relapse rate (ARR) 12 weeks post-partum in women treated with nomegestrol acetate (NOMAc) and 17-beta-estradiol (E2) versus placebo. Methods: POPARTMUS is a randomized, proof-of-concept trial in women with MS, receiving oral NOMAc 10 mg/day and transdermal estradiol 75 µg/week, or placebo. Results: Recruitment was stopped prematurely due to slow inclusions ( n  = 202). No treatment effect was observed on ARR after 12 weeks (sex steroids = 0.90 (0.58–1.39), placebo = 0.97 (0.63–1.50) ( p  = 0.79)). Conclusion: POPARTMUS failed showing efficacy of a NOMAc–E2 combination in preventing post-partum relapses.